Аутсорсинг бізнес-процесів, як засіб підвищення капіталізації підприємства - Манойленко, Олександр Володимирович; Горовий, Дмитро Анатолійович; Строков, Євген Михайлович (Одеський національний економічний університет, 2020)
Метою статті є формування методичних положень щодо запровадження аутсорсингу бізнес-процесів на підприємствах як засобу підвищення капіталізації. У статті обґрунтовано, що аутсорсинг бізнес-процесів, як інструмент делегування певних виробничих або сервісних процесів, дозволяє значно знизити витрати підприємства, визначено основні види аутсорсингу бізнес-процесів, досліджено основні чинники, що заважають впровадженню аутсорсингу на промислових підприємствах – недостатня регламентація бізнес-процесів та відсутність дієвих підходів до оцінки ефективності їх реалізації. Розроблений підхід дозволяє врахувати тип та ступінь стандартизації бізнес-процесів, що плануються для аутсорсингу, глибину їх інтеграції в наскрізний бізнес-процес промислового підприємства; спираючись на об’єкти та сферу застосування бізнес-процесу, він дозволяє обрати варіант проведення аутсорсингу та визначити форми організації спільної діяльності.

The article substantiates that outsourcing of business processes can significantly reduce the costs of an enterprise, as a tool for delegating certain production or service processes. Purpose. The purpose of the article is to formulate the guidelines for the implementation of business processes outsourcing at enterprises as a mean of capitalization increasing. The main types of outsourcing of business processes are identified and their classification is proposed, the main factors that hinder the introduction of outsourcing at industrial enterprises are investigated, such as insufficient regulation business processes and the lack of effective approaches to assessing the effectiveness of their implementation. To overcome these barriers, the structural elements of a methodological approach were determined to organize outsourcing of business processes at an enterprise. They are built on the basis of the typologization and classification of business processes, the choice of forms of organizing joint activities, a description of the business processes of the enterprise, statistical analysis of their indicators, analysis and selection of potential performers. Results. The developed approach allows taking into account the type and degree of standardization of business processes planned for outsourcing, the depth of their integration into the end-to-end business process of an industrial enterprise. Relying on the objects and scope of the business process, it allows choosing the option of outsourcing and determining the forms of organizing joint activities. Conclusions. The proposed approach to the organization of business processes outsourcing makes it possible to enhance significantly the performance of an industrial enterprise, largely, it is the basis for achieving the strategic goal of activity, the increasing of enterprise’s capitalization.
Business process outsourcing as a way to increase the capitalization of an enterprise
Keywords: аутсорсинг; бізнес-процеси; капіталізація підприємств; реінжиніринг; аутсорсер; основні бізнес-процеси; допоміжні бізнес-процеси; outsourcing; business processes; capitalization of the enterprise; reengineering; main business processes; supporting business processes